Pengaruh Kepercayaan, Presepsi Resiko dan Harga terhadap Minat Beli Sepeda Bekas di Wilayah Boyolali - Donna Setiawati; Luki Sri Anggorowati; Nina Afiska Gabriella Salsabila (Lembaga Pengembangan Kinerja Dosen, 2026)
The growth of used bicycle buying and selling businesses in Boyolali Regency has created intense competition, making trust, perceived risk, and price important factors influencing purchase intention. This study aims to analyze the influence of trust, perceived risk, and price, both partially and simultaneously, on purchase intention for used bicycles in Boyolali. This quantitative causality study involved 113 consumers aged 20–45 who had purchased bicycles in Boyolali. Data were collected through a structured Likert-scale questionnaire and analyzed using multiple linear regression to examine the relationships among the variables. The results show that trust, perceived risk, and price, both partially and simultaneously, have a positive and significant effect on purchase intention, with price being the most dominant variable. These findings confirm that increasing trust, managing perceived risk, and setting competitive prices play a significant role in increasing purchase intention for used bicycles in Boyolali. Furthermore, the results provide practical implications for used bicycle sellers to develop effective marketing strategies by strengthening customer confidence, reducing perceived transaction risks, and offering prices that are competitive and aligned with consumers' expectations and purchasing power, thereby improving their competitiveness in the local market.